Determination of yield and yield components of selected tomato varities in soil with different levels of cattle manure application - Maleka, Koena Gideon (University of Limpopo (Turfloop Campus), 2012)
Organic tomatoes are increasingly popular with larger market acceptance since organic farming uses limited or no artificial chemicals. Application of organic fertilisers such as cattle manure has potential to boost organic tomato productivity particularly under low input farming systems. However, information is required on the optimum level of manure application on different tomato cultivars to help emerging tomato farmers in South Africa. The objective of this study was to determine the relative response of yield and yield components among selected determinate and indeterminate tomato cultivars using different levels of cattle manure. Two separate field experiments were conducted at the University of Limpopo during 2007 and 2008 using a split plot design with three replications. Two sets of tomato cultivars were included in which one set consisted indeterminate types (Money Maker, Ox Heart and Sweetie) and the other determinates (Roma and Floradade). Cultivars were assigned as the main plot treatments with six rates of manure (0, 10, 20, 30, 40 and 50 in gram per plant) applied as the subplot treatments to each set. Results indicated significant interactions (P ≤ 0.01) between indeterminate tomato cultivars and levels of manure applied for fruit yield and fruit size in both experiments. Plant height showed variation from 78 to168 cm in Experiment I and 87 to 176 cm in Experiment II. During Experiment I fruit number varied from 23 to 91 per plant and 23 to 97 in Experiment II. Significant differences were detected among determinate cultivars on fruit yield varying from 7928 to 3 4705 kg per hectare during Experiment I and 3 169 to 2 9840 kg per hectare during Experiment II. Overall, the best level of manure for maximum fruit yield and greater fruit size was achieved at 40 g per plant in the indeterminate cultivar Sweetie. Conversely, the best level of manure for maximum fruit yield was achieved at 30 g per plant in determinate cultivar Roma. Thus, to achieve maximum yield, tomato growers could apply 600 and 800 kg per hectare manure on the determinate and indeterminate tomato cultivars, respectively.
Thesis (M.Sc. (Crop Science)) --University of Limpopo, 2012
Keywords: Tomato yield components; Tomatoes; Cattle manure; 635.642; Organic farming -- South Africa; Tomatoes -- Breeding; Crop yields